Development and Preliminary Examination of the Psychometric Properties of the Psychoeducational Group Alliance Scale for Children (PGAS-c) in Two Samples of Children Participating in Groups. Issue 2 (3rd April 2018) - Brouzos, Andreas; Vassilopoulos, Stephanos P.; Baourda, Vasiliki C.
Abstract : Studies examining processes in youth group psychotherapy are scarce. This article reports on the development and psychometric properties of the Psychoeducational Group Alliance Scale for Children (PGAS-c). This scale was designed to assess the therapeutic alliance that develops between the members and the facilitator in a psychoeducational group intervention for children and was tested in 2 samples of children participating in different psychoeducational groups. The PGAS-c was internally consistent in both samples. Concurrent validity was examined using correlations with an established measure of therapeutic relationship (the Barrett-Lennard Relationship Inventory). Reliability and validity of the PGAS-c were supported in both samples.